MAKING HISTORY: A LOOK AT THE ACHIEVEMENTS OF THE WOMEN'S FUTSAL TEAM AT ESCOLA SÔNIA HENRIQUES BARRETO, IN THE MUNICIPALITY OF LARANJAL DO JARI- AP, IN SCHOOL SPORTS (Fiep Bulletin - online, 2024)
Introduction: The current context of Education advocates that the student is the protagonist in the school environment. In this sense, the actions of pedagogical work must ensure the participation of all those involved in the collective work. Objective: reflect on the accomplishments and achievements of the students who are part of the futsal team at the Sônia Henriques Barreto State School, located in the municipality of Laranjal do Jari/Amapá, on the importance of sport at school, addressing the successful experiences of the students in the School Games. Methods: qualitative research, through a case study, with 12 high school students and four physical education teachers, who are part of the state education network in Amapá. For data collection, semi-structured questionnaires and interviews with students and teachers were used. Other sources used were the training observation technique, meetings with parents, friendlies, during the period when the students were participating in the School Games. Results: The titles won are the result of hard work involving students, parents, employees, educators and managers who value sport as an education tool through experiences. The school fulfills its social role in awakening in these students their responsibilities and interests, making them protagonists of their own choices. Conclusion: Works like this instigate debates on the practice of physical education in schools located in stilt houses, focusing on female empowerment, challenges faced by public schools in Amapá, achievements and experiences of students participating in School Games at municipal, state and national levels.
Keywords: futsal; female empowerment; school games; physical education; social vulnerability